Strategy of The Women Empowerment Child Protection and Family Planning Agency (DP3AKB) In The Prevention and Reduction of Stunting in Simeulue Regency - Samliani, Ayu; Handayani, Sri Wahyu (Journal of Social Politics and Governance (JSPG), 2023)
Stunting is a nutritional problem faced by the world, especially poor countries and growing. Malnutrition status in pregnant women is a major factor cause children under five to experience stunting, Simeulue Regency there are 746 toddlers who malnutrition, 8 toddlers who experience malnutrition and there are 1162 toddlers who are stunted. The purpose of this study was to determine stunting prevention strategies conducted by DP3AKB in Simeulue Districh. This research is research qualitative case study approach using in-depth interviews as reference, observation and documentation. (1) provision of diverse, nutritious, balanced, and safe; (2) training/counseling and counseling on nutrition, exclusive breastfeeding, and MPASI; (3) social protection for increasing access of pregnant and lactating mothers and toddlers to health insurance; (4) provision of clean water, sanitation and other appropriateactivities village local needs.